Astigmatism and maternal myopia as important factors affecting success rate of DIMS lens treatment - Christof Meigen; Adrienne Csutak; Patricia Domsa; Éva M Bankó; Judit Körtvélyes; Rita Széchey; Krisztina Lantos; Zoltán Zsolt Nagy (BMJ Open Ophthalmology)
Objective To assess the efficacy of myopia control spectacle lenses (defocus incorporated multiple segments/DIMS) in slowing myopia progression among a diverse Central European paediatric population and investigate the contribution of baseline parameters on treatment outcomes.Methods and analysis This retrospective observational study included 62 individuals aged 4–17 years (mean±SD: 10.21±2.70) with progressing myopia but without ocular pathology with a range of −0.88 to −8.25 D spherical equivalent refraction (SER) (−3.73±1.56), coupled with astigmatism up to −3.25 D cylindrical. All participants were prescribed DIMS (Hoya MiyoSmart) spectacles. Key outcome variables were cycloplegic SER, measured for all participants and axial length (AL), assessed in a subset of patients, recorded at baseline, 6 months and 12 months. Quality of life assessments were conducted at baseline, at 2 weeks, and 3, 6, 9 and 12 months. Additionally, parental myopic dioptre was recorded when applicable.Results At the 12-month mark, myopia progression in patients (mean±SE: −0.40±0.05) mirrored findings from prior European DIMS studies, but with 50% of patients showing no progression. A multivariate analysis of covariance model revealed that baseline astigmatism and younger age adversely affected therapy outcomes in both SER and AL, while severe maternal myopia led to greater SER progression. In contrast, only young age but not astigmatism was associated with AL increase in a comparable group of children with myopia, part of the LIFE Child Study, wearing single-vision spectacles. Patients reported consistent satisfaction with treatment, with minimal side effects, which diminished over the year.Conclusion In the European population, astigmatism, young age and severe maternal myopia are risk factors for suboptimal outcomes following DIMS therapy. Further research is necessary to elucidate the impact of astigmatism on myopic defocus therapy.